2013
DOI: 10.1038/modpathol.2012.233
|View full text |Cite
|
Sign up to set email alerts
|

HPV L1 detection discriminates cervical precancer from transient HPV infection: a prospective international multicenter study

Abstract: The benefits of cytology-based cervical cancer screening programs in reducing morbidity and mortality are well recognized. Especially, overtreatment of human papillomavirus (HPV) high-risk positive early dysplastic lesions may have a negative impact on reproductive outcomes for fertile women. To optimize the clinical management an objective standard is needed to distinguish precancer that requires treatment, from spontaneously resolving HPV infections. In the current study, we examined the prognostic relevance… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 25 publications
(16 citation statements)
references
References 31 publications
0
13
0
Order By: Relevance
“…The differences in clinical performance among the commercially available HPV assays may identify unique subsets of women with very different risk profiles, especially between assays targeting HPV L1-DNA and HPV E6/E7-mRNA. It has been documented that the HPV L1 capsid protein is significantly lower or negative in women with high-grade cervical lesions25 or disease progression 26. Conversely, HPV 16/18 E6/E7 oncoproteins were significantly higher in cervical tissue with high-grade squamous intraepithelial lesions 27.…”
Section: Discussionmentioning
confidence: 99%
“…The differences in clinical performance among the commercially available HPV assays may identify unique subsets of women with very different risk profiles, especially between assays targeting HPV L1-DNA and HPV E6/E7-mRNA. It has been documented that the HPV L1 capsid protein is significantly lower or negative in women with high-grade cervical lesions25 or disease progression 26. Conversely, HPV 16/18 E6/E7 oncoproteins were significantly higher in cervical tissue with high-grade squamous intraepithelial lesions 27.…”
Section: Discussionmentioning
confidence: 99%
“…Using histological sections Galgano et al [17] reported for Cytoactiv a raw agreement and k of 96.9% and 0.88, respectively. With 98% raw agreement and 0.96 for kappa Mehlhorn et al [26] reported similar results for the use of Cytoactiv in cytological samples. Initial L1 studies faced the problem that the sensitivity of randomly choosen L1 antibodies was unacceptable low.…”
Section: Study Resultsmentioning
confidence: 62%
“…We evaluated HPV infection by amplifying a portion of the L1 region of high‐risk HPV, including HPV 16, 18, 31 and 33 in the 40 training and 35 validation samples, using GP5 and GP6 primers as previously reported . Positive PCR amplification was designated as HPV‐L1(+).…”
Section: Methodsmentioning
confidence: 99%